Analysis of optimal options for CO2 emissions reduction in Malaysian transportation sector - Mustapa S.I.; Salleh S.F. (Inderscience Publishers, 2023)
Efficiency; Emission control; Fuels; Linear programming; Motor transportation; Roads and streets; Sensitivity analysis; CO2 emissions; Fuel efficiency improvement; Low carbon; Mitigation measures; Optimisations; Road transport sectors; Transportation sector; Travel demand management; Carbon dioxide; carbon emission; emission control; integrated approach; investment; mitigation; optimization; policy implementation; road transport; traffic emission; transportation; Malaysia